Sistem Pakar Pembagian Harta Waris Menurut Hukum Islam dengan Metode Forward Chaining Berbasis Web - Ilyas Ilyas; Anwardi Anwardi (UIN Sultan Syarif Kasim Riau, 2016)
Developments in science and technology very quickly and rapidly, especially information systems that can provide ease of information. This study gives an overview inheritance information using an expert system which is a branch of artificial intelligence that is able to mimic the way of thinking an expert in solving problems and taking a decision. Limitations of space and time by the speaker and the lack of understanding of ordinary people in terms of inheritance should be a concern, it is necessary to build an application in the form of web-based expert system. This application is built using Artificial Intelligence techniques applied in the form of a Web-based Expert System with forward chaining reasoning methods to solve the problem, despite the absence of an expert / specialist. This web-based implementation using PHP programming language as a tool of expert system builders and MySQL as the database. In this application people can calculate the division of inheritance by looking directly argument. besides that people can also calculate the part of the property division performed. The processes above is done according to the rules (rule) that is based on the Qur'an, hadith and ijma 'ulama which is the basis of Islamic law. Expert System is expected to facilitate the public in making the division of inheritance according to Islamic Shariah. Because of the division of inheritance is one of the laws that are clear in the Qur'an. Keywords: inheritance, MySQL, information systems, expert systems